High-Level Circulating Total Calcium and Low Phosphate as Predictors of Insulin Resistance among Non-Diabetic Taxi-Motorbike Drivers Living and Working in Cotonou, Benin - AVOGBE, PATRICE HODONOU; SANNI, AMBALIOU (My University, 2022)
Insulin resistance (IR) is a well-recognized marker of increased cardiovascu- lar diseases (CVDs) and type 2 diabetes (T2D) risk. Therefore, screening for IR predictors would help reduce the likelihood of progression from early stage of IR to T2D or CVDs. However, the knowledge of association between IR and circulating total calcium (CTCa) and phosphate levels among non- diabetic patients in Benin is lacking. We investigated whether CTCa and phosphate levels within the normal ranges are associated with IR risk among taxi-motorbike drivers (TMDs) living and working in Cotonou. We evaluated 134 non-diabetic TMDs (aged 22 - 59 years) based on CTCa, phosphate, glu- cose, fasting insulin, and IR levels. IR was assessed using the homeostatic model assessment-insulin resistance (HOMA-IR). IR was defined as the 75th percentile of HOMA-IR value. Cardiometabolic factors were analyzed by ter- tiles of CTCa and phosphate levels (low, middle, and high groups). Logistic regression models evaluated the relationships between IR and CTCa and phosphate levels. Our results showed that participants with high CTCa levels had the highest prevalence of IR, elevated total cholesterol and high-density lipoprotein cholesterol. In a fully adjusted model, the odd ratio (OR) of hav- ing IR comparing the highest (>2.50 mmol/L) to the lowest CTCa levels (<2.43 mmol/L) was 6.62 (p = 0.003). In contrast, IR level decreased as the phosphate levels increased. The OR for IR comparing the highest (>1.23 mmol/L) and the lowest levels (<1.10 mmol/L) of phosphate was 0.28 (p = 0.037). In conclusion, our study demonstrates that elevated CTCa and low phosphate levels are significant predictors of IR in non-diabetic patients. Continuous monitoring of these markers may help identify earlier individuals at greatest IR risk.
Keywords: Blood Glucose; Insulin Resistance; Circulating Total Calcium; Phosphate; Taxi-Motorbike Drivers